Effect of water to cement ratio, fly ash, and slag on the electromagnetic shielding effectiveness of mortar. (30th September 2020) - Wanasinghe, Dimuthu; Aslani, Farhad; Ma, Guowei
Highlights: Mechanical property change due to additives correlates with finding in literature. Electrical conductivity of cementitious composites increases with the W/C ratio. High W/C ratio reduces the EMI shielding properties in cementitious composites. A moderate amount of FA and GGBFS is needed for optimal EMI shielding. EMI shielding of investigated mixes increases with the frequency. Abstract: Electromagnetic (EM) shielding has become an important aspect in the modern world as the increased usage of electronic devices has a profound effect on the risk of EM pollution within the atmosphere and the harmful effects of EM on humans. In the recent decade, there has been an increased number of research focusing on using cementitious materials to be used as EM shielding materials. Many of these researches have focused on the addition of various additives into the cementitious mix to increase the EM shielding properties. This work investigates the effect of water to cement (W/C) ratio and primary additives such as fly ash (FA) and ground-granulated blast-furnace slag (GGBFS) on the EM shielding. Wide range of properties including mechanical, electrical conductivity, EM shielding, and microstructural properties were analysed to identify the ideal W/C ratio, FA, and GGBFS content that would result in higher shielding with adequate mechanical properties. Electromagnetic shielding tests were carried out in accordance with ASTM D4935 – 18 standards within 30 MHz to 1.5 GHz frequency range. Test results show that the ideal W/C ratio in cementitious composites for an optimal EM shielding amount of 1.89 dB, should be 0.3. For the mixes with additives, maximum EM shielding amounts of 3.38 dB and 5.06 dB were obtained at a frequency of 1.5 GHz, when the FA content was 1.8 with a W/C ratio of 0.4 and GGBFS content of 1.2 with a W/C ratio of 0.4, respectively.